2012
DOI: 10.1309/ajcp6vdbl4brxrqa
|View full text |Cite
|
Sign up to set email alerts
|

NRP-1/CD304 Expression in Acute Leukemia

Abstract: Neuropilin-1 (NRP-1)/CD304 is a marker for plasmacytoid dendritic cells. We determined the distribution of NRP-1/CD304 expression on normal hematopoietic cells and in 167 acute leukemias by flow cytometry. NRP-1/CD304 surface expression was frequent in precursor B-cell acute lymphoblastic leukemia (36/51 [71%]) and uncommon in acute myeloid leukemia (22.9%). In acute myeloid leukemia, expression was noted in all (4/4) acute myeloid leukemias with the M4eo subtype and in 50% of specimens (6/12) with complex cyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 21 publications
(47 reference statements)
4
13
0
Order By: Relevance
“…This datum is in agreement with Meyerson et al 2012 22 who found that Neuropilin-1 is frequently expressed on B-ALL blasts, and weakly expressed in normal bone marrow B-cell progenitors, while gradually decreasing during maturation, to be completely lost at later stages of B-cell. The expression of Neuropilin-1 on B-cell progenitors may explain its frequent higher expression in precursor B-ALL than mature ALL .…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…This datum is in agreement with Meyerson et al 2012 22 who found that Neuropilin-1 is frequently expressed on B-ALL blasts, and weakly expressed in normal bone marrow B-cell progenitors, while gradually decreasing during maturation, to be completely lost at later stages of B-cell. The expression of Neuropilin-1 on B-cell progenitors may explain its frequent higher expression in precursor B-ALL than mature ALL .…”
Section: Discussionsupporting
confidence: 92%
“…This is in agreement with Karjalainen et al 2011 17 who examined Neuropilin-1 in patients with acute leukemia and demonstrated its expression, above baseline bone marrow levels, in all B-cell ALL samples and in two thirds of AML samples with stronger expression in blast cells of B-cell ALL than AML blast cells. 17 Similarly, Meyerson et al 2012 22 found that Neuropilin-1 is frequently expressed on B-ALL blasts (71%), whereas its expression is less frequent on AML blasts (22.9%) and consistently absent on peripheral blood lymphocytes. 22 …”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Pathologically, the upregulation of NRP-1 has been found in a variety of tumor cells and has been demonstrated to be involved in tumorigenesis and tumor progression. For example, Meyerson et al [21] reported that NRP-1 was overexpressed in precursor B-cell acute lymphoblastic leukemia samples compared with normal B-cell progenitors, allowing for its potential use as a marker for the detection of minimal residual disease; Li et al [22] demonstrated that NRP-1 was overexpressed in glioblastoma and may be an attractive candidate as a therapeutic target for this disease; Xu et al [23] indicated that NRP-1 may be able to promote the growth of hepatocellular carcinoma in vitro and in vivo, and therefore may be considered as a novel therapeutic target for this carcinoma; Hansel et al [24] found the increased expression of NRP-1 in gastrointestinal adenocarcinomas and in a subset of high-grade precursor lesions, which appears to parallel invasive behavior and may therefore be used as a potential marker for cancer aggressiveness; Baba et al [25] reported that the enhanced expression of NRP-1 may be not only associated with oncogenesis, but also with ovarian cancer malignancy, and this molecule may be a targeting candidate for the treatment of ovarian malignancies; Stephenson et al [26] also suggested that the upregulation of NRP-1 may be involved in the induction of local invasiveness of neoplasia and angiogenesis and have direct relevance to the progression of breast cancer. In line with these previous studies, our immunohistochemistry analysis also found the overexpression of NRP-1 in NPC tissues compared with non-cancerous nasopharyngeal tissues.…”
Section: Discussionmentioning
confidence: 99%